O trem-de-ferro e o cinema em Motes Claros-MG: a projeção de um divertimento pelos trilhos do sertão mineiro - Rogério Othon Teixeira Alves (2019)
The objective is to discuss the modifications experienced in the cinema of Montes Claros-MG and what it has influenced on a share of the population’s entertainment habits, fundamentally after the implementation of the Central Brazilian Railroad Station in 1926. The necessary data was searched on journals from 1920 and on, as well as on pieces by memoir writers who focused on the cinema of that time. Apparently, it is evident the correlation between the development of the experience of the cinema in Montes Claros-MG (regarding aspects like access, quantity and quality of films, equipment quality, as well as its permanent maintenance) and the railroad beginning in 1926.